SOME QUESTIONS OF LAW IN THE STATE LANGUAGE - Khamzina Назгүл Амантайқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article discusses questions about the language of law, authenticity of terms used in the legislation.